HUMAN RESOURCE MANAGEMENT EFFICIENCY STUDY GUIDELINES OF PRIVATE UNIVERSITIES IN GUANGXI PROVINCE, PEOPLE’S REPUBLIC OF CHINA - Gisieng, Yian; Suteeniran, Niran; Wimuttipanya, Jittawisut; Sittiwiset, Sahasaya (Journal of MCU Nakhondhat, 2023)
The purpose of study on 1) to study the efficiency of human resource management of private universities in Guangxi Province People's Republic of China 2) to assess the efficiency of human resource management of a private university in Guangxi Province, People's Republic of China. 3) To study the efficiency of human resource management of a private university in Guangxi Province, People's Republic of China. The sample group were administrator and teachers in Guangxi province, people’s republic of China. They were selected by purposive sampling method 20 people from each university, totaling 480 people. The interview group was the president or vice president of the university. 1 person per university, totaling 24 people. The group of appraisers for the suitability of the implementation consisted of experts from the university. and those who have main roles in policy and strategic management, totaling 20 people. The data were collected by using 5-point rating scale questionnaire and were statistically analyzed in percentage, mean, and standard deviation. The finding of the study. Personnel responsible for recruitment have clearly defined guidelines for recruitment and appointment of personnel according to regulations and are able to attract qualified personnel who match the job and are interested in joining the organization effectively by Decide the person with the most suitable qualifications and abilities from the candidates. in order to come to work and hold the desired position The organization has encouraged all personnel to have the opportunity to Enhance knowledge, skills, experiences and study visits to continually develop worldviews.